Zastosowanie Transformacji Laplace'a w Obliczeniach Reologicznych Konstrukcji Sprężonych - C. Eimer (Engineering Transactions, 1958)
Establishment of principles of practical computation of the variation of mechanical quantities in function of time in prestressed statically indeterminate structures on the basis of the general theory described in the Ref. [1]. The creep function is assumed in the form (1.1). The solution is obtained by means of the operational method using the Laplace transformation. Approximate methods are proposed enabling us to determine with a desired degree of accuracy the influence of the prestressing reinforcement. As an example, a rectangular doubly hinged frame is considered, taking into account the influence of both the moments and the longitudinal forces.